Optical properties of monolithic zirconia crowns: In vitro and In vivo evaluation - Koci Brunilda; Dedaj Edlira; Koci Nazmi (Balkan Stomatological Society, 2022)
Background/Aim: The aim of this study was to compare the monolithic and layered zirconia crowns by their optical property of translucency, using in vitro and in vivo evaluation methods. Material and Methods: One upper incisor and one canine were prepared to receive 6 monolithic Lava Plus HT and 6 layered Lava crowns using the CAD/CAM technology. The translucency in the vitro evaluation, was determined using a digital photoradiometer to measure the light reflected by the crowns in two different conditions, natural and metal plated abutment tooth. A provisional complete prosthesis of an edentulous patient, with the abutment teeth mounted in their anatomical position, was used for the in vivo evaluation. The crowns were randomly placed and evaluated by two independent operators in the oral cavity conditions. Results: In vitro results showed that monolithic crowns were not significantly less translucent than layered ones in both incisor (p=0.098) and canine (p=0.340): contrast ratio 0.978 vs. 0.956 and 0.941 vs. 0.929, respectively (Student -t test; a=0.05). In vivo evaluation results showed that the difference in the luminance was not statistically significant between Lava Plus HT and layered Lava crowns according to Mann Whitney Test, p=0.089 (a=0.01). Conclusions: The difference in translucency between monolithic and layered zirconia crowns was not statistically significant both in vitro and in vivo evaluation. Monolithic zirconia had a good masking ability of the abutment tooth.